Multidimensional Financial Inclusion Index for the Scheduled Tribes of Kerala - K., Reshma; K., Kanniammal (Indian Journal of Finance, 2025)
Purpose : The present study aimed to develop a novel financial inclusion index (FII) that could be applied to measure the level of financial inclusiveness of scheduled tribes of Kerala and to estimate and compare the degrees of financial inclusivity among Kerala’s scheduled tribe communities using index values. Methodology : The study computed the FII for 21 distinct communities of scheduled tribes residing in Kerala by suggesting an exclusive multidimensional index for financial inclusivity. Finding : The FII showed a minor improvement in a few populations, with the Malappuram and Palakkad tribes having poor financial inclusion. Communities with more financial inclusion typically had higher human development index (HDI) and literacy rates. However, just a handful progressed from weak to mid-inclusion, while low HDI, widespread illiteracy, and insufficient banking facilities hampered higher inclusion levels. Practical Implications : Structural changes to the policy framework were necessary to ensure that all communities had an equal degree of financial inclusivity and offered monetary services to the poorest of the poor at no cost or a reduced cost in order to promote sustainable, inclusive growth. Originality : This research introduced a novel multidimensional financial inclusion index (MFII) that was specifically designed to assess the financial inclusion of Kerala’s scheduled tribes, incorporating both supply- and demand-side indicators to deliver a comprehensive evaluation of their financial access and participation.